Time‐resolved interaction proteomics of the GIGANTEA protein under diurnal cycles in Arabidopsis. Issue 3 (28th December 2018) - Krahmer, Johanna; Goralogia, Greg S.; Kubota, Akane; Zardilis, Argyris; Johnson, Richard S.; Song, Young Hun; MacCoss, Michael J.; Le Bihan, Thierry; Halliday, Karen J.; Imaizumi, Takato; Millar, Andrew J.
Abstract : The plant‐specific protein GIGANTEA (GI) controls many developmental and physiological processes, mediating rhythmic post‐translational regulation. GI physically binds several proteins implicated in the circadian clock, photoperiodic flowering, and abiotic stress responses. To understand GI's multifaceted function, we aimed to comprehensively and quantitatively identify potential interactors of GI in a time‐specific manner, using proteomics on Arabidopsis plants expressing epitope‐tagged GI. We detected previously identified (in)direct interactors of GI, as well as proteins implicated in protein folding, or degradation, and a previously uncharacterized transcription factor, CYCLING DOF FACTOR6 ( CDF6 ). We verified CDF6's direct interaction with GI, and ZEITLUPE/FLAVIN‐BINDING, KELCH REPEAT, F‐BOX 1/LIGHT KELCH PROTEIN 2 proteins, and demonstrated its involvement in photoperiodic flowering. Extending interaction proteomics to time series provides a data resource of candidate protein targets for GI's post‐translational control. Abstract :